The legal status of juveniles in civil proceedings (Journal of actual problems of jurisprudence, 2018)
In this article is considered the questions of legal capacity and capability of minors in civil proceedings. On the basis of analysis of the rules of procedural and substantive law determined particular qualities of legal status of the three age categories of minors in civil cases. The current tendency of development of legislation is characterized by strengthening the procedural status of minors as full participants in civil proceedings.Key words: civil procedure, court, part, legal capacity, capability, juveniles (minors).